Cardiovascular Oncology: The Need for a Multidisciplinary Approach - Ortega Pérez, Rodrigo; Pardo Sanz, Ana; García Gutiérrez, Valentín; Zamorano Gómez, José Luis (Seminars in Thrombosis and Hemostasis, 2021)
Improved cancer survivorship has led to an increase in cardiovascular (CV) complications in the oncologic population, mainly associated with therapeutic regimens. Hence, cardio-oncology has grown toward unifying the cancer care process in which the best prevention, early detection, treatment, and CV surveillance are offered to patients. This multidisciplinary approach allows us to optimize and agree upon clinical decisions to enhance clinical outcomes. Atrial fibrillation is one of the hot topics in the field because it is still challenging in cancer patients. The optimal antithrombotic therapy remains unclear. Nevertheless, evidence supports that specific recommendations are needed due to a hemorrhagic/thrombotic disbalance present within this subgroup of patients and a low rate of anticoagulation treatments compared with the general population. Further, cardiotoxicity management is currently transforming. Increasingly, early detection of subclinical alterations is raising awareness. When medical therapy is initiated early, fewer patients progress to ventricular dysfunction and the rate of patients completing cancer therapy gradually increases. New approaches are demonstrating better outcomes and these strategies will expectedly be established in clinical practice. Cardio-oncology enables us to find the best balance between cancer treatment and CV health protection. Nowadays, more and more physicians are being instructed in this discipline, which gradually exhibits a greater presence in conferences and scientific journals. However, given the need for physicians thoroughly trained in cardio-oncology, this subspecialty must be promoted further.
Keywords: Cardio-oncology; multidisciplinary approach; cardiotoxicity; atrial fibrillation